Organizational factors associated with community therapists’ self-efficacy in EBP delivery: The interplay between sustainment leadership, sustainment climate, and psychological safety - Y. Vivian Byeon; Anna S. Lau; Teresa Lind; Alison B. Hamilton; Lauren Brookman-Frazee (Implementation Research and Practice, 2022)
Background Inner context organizational factors proximally shape therapist experiences with evidence-based practice (EBP) implementation and may influence therapist self-efficacy, which has been linked to sustained use of EBPs in community mental health settings. Research has primarily focused on constructs such as implementation leadership and climate. However, the effects of such factors may depend upon other inner context dimensions, such as psychological safety. Psychologically safe environments are conducive to taking risks, speaking up about problems, and requesting feedback and may promote therapist self-efficacy during implementation. This study examines whether organizational sustainment leadership and sustainment climate relate to therapist EBP self-efficacy only under conditions of psychological safety. Methods Data were collected from 410 clinicians in 85 programs during the sustainment phase of a system-driven implementation of multiple EBPs in children's mental health services. Therapists reported on their organization's sustainment leadership, sustainment climate, psychological safety, and their own self-efficacy in delivering specific EBPs. Multilevel regression analyses were conducted to account for nested data structure. Results Among program-level variables, sustainment leadership and psychological safety both significantly predicted therapist self-efficacy. However, there were no significant interactions between program-level sustainment climate and psychological safety. Exploratory post-hoc analyses revealed a significant interaction between program-level sustainment leadership and therapist-level perceptions of psychological safety such that that the conditional effect of psychological safety on EBP self-efficacy was significant at high levels of sustainment leadership, but not at low or average levels. Conclusion We noted independent links between sustainment leadership, organizational psychological safety and therapists feelings of confidence and mastery with EBPs. Therapists’ individual perceptions of psychological safety were linked to self-efficacy only in programs with high sustainment leadership. Thus, sustainment leadership and psychological safety may both represent implementation intervention targets, but it may not be critical to assess for perceptions of psychological safety before deploying organizational leadership strategies. Plain language abstract Therapist self-efficacy is a therapist's belief that they are capable, knowledgeable, and skilled enough to deliver evidence-based practices (EBPs), and is thought to promote improved clinical and implementation outcomes, such as therapists’ sustained use of EBPs. Conditions within community mental health organizations may influence therapists’ sense of EBP self-efficacy. Leaders’ support and expectations for EBP implementation, and collective staff perceptions about the organization's climate to support EBPs are linked to positive therapist attitudes and EBP adoption. However, less is known about how these implementation-specific organizational factors associated with therapist EBP self-efficacy in the long-term, and how this may depend on general workplace conditions. Specifically, psychologically safe environments – where therapists feel safe taking risks such as asking questions, admitting mistakes, and trying new skills – may be needed to promote self-efficacy when therapists are tasked with learning and using complex multi-component EBP innovations. The current study tested the prediction that leader-driven and program-wide focus on EBP sustainment may promote therapist EBP self-efficacy only in organizations where conditions for learning are psychologically safe. Our findings confirmed that fostering strong sustainment focused leadership and psychologically safe environments may each be important for increasing therapists’ EBP self-efficacy. The model results suggested that individual therapist perceptions of psychological safety were more strongly related to EBP self-efficacy in programs with greater implementation leadership. Findings suggest the importance of increasing EBP leadership behavior to fully potentiate other facilitating conditions for therapist learning in the sustainment phase of EBP implementation initiatives.